Extensive vs. intensive margin in Germany and the United States: any differences? - Christian Merkl; Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2009)
This paper analyzes the role of the extensive vis-à-vis the intensive margin of labor adjustment in Germany and in the United States. The contribution is twofold. First, we provide an update of older U.S. studies and confirm the view that the extensive margin (i.e., the adjustment in the number of workers) explains the largest part in the overall variability in aggregate hours. Second, although the German labor market structure is very different from its U.S. counterpart, the quantitative importance of the extensive margin is of similar magnitude.
Keywords: C10; E32; J21; 330; Business Cycle; Extensive and Intensive Margin; Variance Decomposition; Arbeitsnachfrage; Konjunktur; Kündigung; Arbeitszeitflexibilisierung; Kündigungsschutz; Vergleich; Schätzung; USA; Deutschland